From Benito Mussolini to Hugo Chavez : intellectuals and a century of political hero worship - Hollander, Paul 1932- (Cambridge University Press, 2016)
Introduction: intellectuals and politics -- Mussolini, fascism and intellectuals -- Hitler, nazism and intellectuals -- Stalin, Rakosi, Soviet communism and intellectuals -- Castro, Che Guevara, and their western admirers -- Western intellectuals, Mao's China and Cambodia under Pol Pot -- Other dictators and their admirers in more recent times -- Conclusions: the personal and the political